[RETRACTED]Karakteristik Gangguan Tidur pada Usia Produktif dan Usia Pertengahan - Soleh Amini Yahman; Setiyo Purwanto; Nisa Rachmah Nur Anganti (Jurnal Penelitian Humaniora, 2021)
The article titled “Karakteristik Gangguan Tidur pada Usia Produktif  dan Usia Pertengahan” ([version 1; peer review: 1 not approved] F1000Research 2019, 8: 396 http://10.23917/humaniora.v22i2.13555) has been retracted by F1000Research on the grounds of scientific misconduct.   On submission to F1000Research, all manuscripts undergo plagiarism checks as standard—this is detailed in our Originality policies. Upon submission, authors are also required to declare that the article is not under consideration or review by another publisher. At this stage in the publication process, our plagiarism detection software did not identify any significant duplication of text. On investigation, the extent of overlap between these two publications was substantial, and this was deemed a case of duplicate publication. Duplicate publication is a major ethical issue and, as a member of the Committee on Publication Ethics (COPE) and a follower of the Jurnal Penelitian Humaniora (JPH) recommendations, F1000Research takes such matters seriously. In response to our concerns, corresponding author Soleh Amini acknowledged that publication misconduct has taken place and has been informed that, due to the extent and nature of duplication between the articles published in F1000Research and IOP, F1000Research will retract the article and publish a linked retraction notice.   In line with COPE guidelines, F1000Research has informed the Publisher of IOP Conference Series about this issue, and our final decision has been communicated to all authors and their respective institutions.